Electrochemical and Morphological Characterization of Zn−Al−Cu Layered Double Hydroxides as a Negative Electrode in Aqueous Zinc‐Ion Batteries. Issue 15 (9th July 2018) - Bani Hashemi, A.; Kasiri, G.; Glenneberg, J.; Langer, F.; Kun, R.; La Mantia, F.
Abstract: The front cover artwork is provided by Universität Bremen, Energy Storage and Energy Conversion Research Group and Innovative Sensor and Functional Materials Research Group. The image shows how layered double hydroxides can contribute to the improvement of the performances of the zinc anode in aqueous zinc‐ion batteries for the short‐term storage of renewable energies. Read the full text of the Article at10.1002/celc.201800291 . Abstract : " A copper‐doped Zn‐Al‐CO3 layered double hydroxide was synthesized by a co‐precipitation method under constant pH and was investigated as a suitable sold‐state additive in zinc‐based negative electrodes .. ." Find out more about the story behind the front cover research at10.1002/celc.201800309 .